The Effect of Sham Feeding on Neurocardiac Regulation in Healthy Human Volunteers - Markad V Kamath; Robert Spaziani; Sangeeta Ullal; Gervais Tougas; Juan C Guzman; Carlos Morillo; Joshua Capogna; Mohammed Al-Bayati; David Armstrong (Canadian Journal of Gastroenterology)
BACKGROUND: Distension and electrical stimuli in the esophagus alter heart rate variability (HRV) consistent with activation of vagal afferent and efferent pathways. Sham feeding stimulates gastric acid secretion by means of vagal efferent pathways. It is not known, however, whether activation of vagal efferent pathways is organ- or stimulus-specific.